A combinatorial approach towards achieving an injectable, self-contained, phosphate-releasing scaffold for promoting biomineralization in critical size bone defects. (1st January 2016) - Nayef, Lamees; Mekhail, Mina; Benameur, Laila; Rendon, Juan S.; Hamdy, Reggie; Tabrizian, Maryam
Graphical abstract: Delivery of BMP-7, and PPtase especially, from injectable GDP cross-linked chitosan sponge increase mineralization in vitro, proving to be a promising candidate for drug delivery in bone regeneration applications. Abstract: An injectable, guanosine 5′-diphosphate (GDP)-crosslinked chitosan sponge was investigated as a drug delivery system (DDS) for accelerating biomineralization in critical size bone defects (CSBDs). Two approaches were examined both individually, and in combination, in order to achieve this goal. The first approach involved the encapsulation and release of Bone Morphogenetic Protein 7 (BMP-7), a powerful mineralization stimulant. Results confirmed that the rapid gelation of the chitosan sponge prompted high encapsulation of BMP-7 and provided a controlled release over a period of 30 days with no burst release. The second approach was aimed at encapsulating pyrophosphatase (PPtase) in the chitosan sponge to cleave pyrophosphate (PPi) – a mineralization inhibitor and a degradation by-product of the chitosan sponge – into phosphate ions (Pi). PPtase was successfully encapsulated in the chitosan sponge and was able to completely eliminate PPi from the media by cleaving them to Pi. Chitosan sponges releasing Pi into the media were shown to increase overall biomineralization fourfold as compared to controls, an amount equivalent to biomineralization caused by direct injection of 1 μg of free BMP-7 to the cells. Even though the combined encapsulation of 1 μg BMP-7 and PPtase in the sponges did not demonstrate an additional increase in biomineralization, encapsulation of low concentrations of BMP-7 can promote mesenchymal stem cell migration into the sponge after application in vivo. The findings suggest that the sponge-PPtase system likely allows excellent bone regeneration with lower concentrations of BMP-7, reducing risks and expense of the treatment. Statement of significance: There are bone defects, known as critical size defects, which do not heal on their own and require a therapeutic intervention. The current commercially-available therapies use large quantities of growth factors, such as Bone Morphogenetic Proteins (BMPs), which makes them expensive and a source for a myriad of unwanted side effects. In this manuscript we demonstrate, for the first time, the use of an injectable chitosan-based sponge that contains no inorganic components, but can nonetheless act as a source of phosphate ions to improve bone mineralization. We also demonstrate that this sponge can entrap small concentrations of BMP-7 and provide controlled release over time. The ability to release phosphate ions and low concentrations of BMP-7 makes this therapeutic intervention clinically-relevant, affordable, and safe.